Ceftriaxone ameliorates cyclosporine A-induced oxidative nephrotoxicity in rat - Yilmaz, Nigar; Ilhan, Selcuk; Naziroglu, Mustafa; Oktar, Suleyman; Nacar, Ahmet; Arica, Vefik; Tutanc, Murat (Wiley, 2011)
A growing body of evidence now suggested that cyclosporine A (CycA)-induced nephrotoxicity is a crucial clinical problem and oxidative stress is importantly responsible for its toxicity. Ceftriaxone induced antioxidant effect in brain and neuronal tissues against oxidative damage although its antioxidant potential effect on kidney has not been clarified. The aim of this study was to evaluate whether ceftriaxone protects CycA-induced oxidative stress kidney injury in rats. Twenty-four rats were equally divided into four groups. First group was used as control. Ceftriaxone (200 mg/kg) and CycA (15 mg/kg) were administrated to second and third groups for 10 days, respectively. The ceftriaxone and CycA combination was given to rats constituting the fourth group for 10 days. Lipid peroxidation (LP), urea nitrogen and lactate dehydrogenase (LDH) levels were higher in CycA group than in control and ceftriaxone groups although LP, urea nitrogen and LDH levels were lower in ceftriaxone + CycA group than in control and ceftriaxone groups. Glutathione peroxidase and catalase activities were lower in CycA group than in control whereas their activities were increased in control and ceftriaxone groups. Superoxide dismutase activity did not change by the treatments. Ceftriaxone administration recovered also CycA-induced atrophy, vacuolization and exfoliations of tubular epithelium and glomerular collapse in histopathological evaluation of kidney. In conclusion, we observed that ceftriaxone is beneficial on CycA-induced oxidative stress in kidney of rats by modulating oxidative and antioxidant system. Copyright (C) 2011 John Wiley & Sons, Ltd.
Keywords: ceftriaxone; cyclosporine A; nephrotoxicity; oxidative stress; glutathione peroxidase; histology; kidney